Pengaruh Video Pembelajaran Materi Hati Nurani: Memilih Yang Benar Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Kelas VII SMP Negeri 4 Pahae Julu - Mey Lenna Panggabean; Robinhot Sihombing; Malani Simanungkalit (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this research is to determine the effect of learning videos on conscience material: choosing the right on student learning outcomes in Christian Religious Education and Character Education subjects in class VII SMP N 4 Pahae Julu. The research hypothesis is: